Penilaian Kepuasan Penumpang Terhadap Ketersediaan Fasilitas Tempat Makan Sebagai Fasilitas Penunjang Bandara Pasca Pandemi Covid 19 Di Bandar Udara Internasional Juanda Surabaya - Rita Bastianita Sarah; Fryda Fatmayati (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Airport supporting facilities are facilities that directly and indirectly support airport activities and provide added economic value to airport operations. One of the supporting airport facilities is a place to eat. Places to eat are no less important because apart from the waiting room, places to eat are also a direct destination and gathering of flight service users. With the continuing increase in the number of passengers arriving at Juanda International Airport in Surabaya after the Covid 19 pandemic, resulting in passenger density, but airport facility services are still limited. Because many souvenir shops and places to eat are closed. The approach used in this study is a quantitative approach where the results of the study use descriptive quantitative methods. Quantitative research is a method in which the research data is in the form of 2 numbers and is analyzed using statistics with the aim of testing the hypotheses that have been set. The purpose of testing the T hypothesis is to determine whether there is a joint effect between the independent variable (X) on the dependent variable (Y). Significance value (Sig.) is the result of the T test. Which means Ho is rejected and the calculated T value is 12.628 greater than F table 1.671, indicating that Ha is accepted. The consequence of the T test states that in this study, the Availability of Dining Facilities affects the existence of Passenger Satisfaction at Juanda International Airport in Surabaya. Based on the test results for the coefficient of determination, the R square (R2) value is 0.727. Shows that the variable availability of dining facilities has an effect of 72.7% on passenger satisfaction. This shows that the independent variable the availability of dining facilities has a major effect on passenger satisfaction at Juanda International Airport Surabaya.